Clinical and epidemiological analysis of COVID-19 in End-Stage Renal Disease patients undergoing maintenance hemodialysis: A study from Golestan province - Samira Juibari; Anna Rashedi; Mohammad Mojerloo; Zeinab Mohammadi; Saied Amirkhanlou (Jorjani Biomedicine Journal)
Background: End-Stage Renal Disease (ESRD) patients under maintenance hemodialysis are at higher risk for COVID-19 and severe outcomes. This study aimed to investigate the association between ESRD patients who underwent maintenance hemodialysis at 5th Azar and Sayad Shirazi Hospital in Golestan Province in 2019 and their risk of contracting and experiencing severe outcomes from COVID-19. Furthermore, this study aimed to provide insights into the epidemic status of COVID-19 in this specific population, contributing to better insight into the unique challenges faced by ESRD patients on hemodialysis during the pandemic. Methods: This retrospective descriptive cross-sectional study was performed on patients who underwent maintenance hemodialysis. The diagnosis was made based on diagnostic criteria and COVID-19 PCR test. Medical information of all participants was collected. Medical information including clinical, laboratory, and radiological data as well as morbidity and mortality were collected and analyzed by experts. Statistical analysis was performed using SPSS version 21. Normality was evaluated using Shapiro-Wilk test and comparison between groups was analyzed using student T-test and Mann-Whitney U tests (p <0.05). Results: The highest radiological view was related to the ground glass view with 46.7% and Linear Opacities with 26.7%. Most patients (86.6%) were discharged and four of them (13.4%) passed away. WBC, creatinine, and age were significantly associated with ESRD patients’ mortality (p <0.05). The patients who passed away were old and had higher levels of WBC and creatinine (p > 0.05). No significant difference was observed between the age and BMI of passed away and discharged patients. None of the laboratory parameters in the two groups of passed away and discharged patients with COVID-19 showed a significant difference (p> 0.05). Patients with COVID-19 who had a history of diabetes and hypertension, clinical symptoms, such as cough (p=0.049), weakness, and lethargy (p=0.05), indicated a significant difference in mortality compared to the group that was discharged (p <0.05). Conclusion: ESRD patients who underwent hemodialysis due to their underlying problems and the crowded environment of dialysis wards more than the general population are at risk of getting COVID-19.